2003
DOI: 10.1136/jnnp.74.5.570
|View full text |Cite
|
Sign up to set email alerts
|

Influence of clinical, demographic, and socioeconomic variables on quality of life in patients with epilepsy: findings from Georgian study

Abstract: Objective: To identify the clinical, demographic, and socioeconomic factors that are associated with a poor quality of life in patients with epilepsy in Georgia. Methods: Clinical, demographic, and socioeconomic status data were collected from 115 adult epileptic outpatients being treated in the epilepsy programme at the Sarajishvili Institute of Neurology and Neurosurgery (SINN) in Tbilisi, Georgia. Health Related Quality of Life (HRQL) was measured by the Quality of Life in Epilepsy Inventory (QOLIE-31). Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
85
9
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(114 citation statements)
references
References 10 publications
12
85
9
8
Order By: Relevance
“…The differences were highly statistically significant on ANOVA (p value<0.001).This shows that education improves quality of life. Similar results were reported by Choi-Kwon S et al 11 Frequency of seizures per month was positively correlated with QOLIE-9 total scores (Pearson Correlation 0.622) and was highly statistically significant (p value <0.001), as also reported by Djibuti et al and Thomas et al 2,10 Duration of illness positively correlated with QOLIE-9 total scores (Pearson Correlation 0.118) and but was statistically insignificant (p value 0.242). Szaflarski et al found poor quality of life with increase duration of illness.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The differences were highly statistically significant on ANOVA (p value<0.001).This shows that education improves quality of life. Similar results were reported by Choi-Kwon S et al 11 Frequency of seizures per month was positively correlated with QOLIE-9 total scores (Pearson Correlation 0.622) and was highly statistically significant (p value <0.001), as also reported by Djibuti et al and Thomas et al 2,10 Duration of illness positively correlated with QOLIE-9 total scores (Pearson Correlation 0.118) and but was statistically insignificant (p value 0.242). Szaflarski et al found poor quality of life with increase duration of illness.…”
Section: Discussionsupporting
confidence: 79%
“…In this study mean QOLIE-9 total scores were higher in women (21.03) than men (19.17) but not statistically significant (p value 0.081). 10 Mean QOLIE-9 total scores were 16.66, 19.74, 20.13 and 24.00 in married, widows, unmarried and separated individuals respectively. The differences in the means were statistically significant on ANOVA (p value 0.002).This implies that marriage confers some benefit to quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to some studies 10 , no significant difference was found in the QoL due to the other socio-demographic aspects studied, although other papers 5,[7][8][9]15 reported that an elevated age and low scholastic level were related to a worse QoL.…”
Section: Qol and The Socio-demographic And Clinical Aspectsmentioning
confidence: 67%
“…dimensions of cognitive function, energy/fatigue and overall score, a fact already documented in the literature [4][5][6]9,10,13,16 . Besides, a sustained improvement in QoL was associated with long-term absolute freedom from ES 4,11 .…”
Section: Qol and The Socio-demographic And Clinical Aspectsmentioning
confidence: 70%
See 1 more Smart Citation